The Effect of Oil Palm Farming Production on the Provision of People's Business Credit, Land Area, and Fertilizers in Langkat Regency - Veronika Halawa; Nelva Ginting; Anita Rizky Lubis; Suwandy Purba; Indra Budiman (Proceeding of The International Conference on Economics and Business, 2022)
The development of oil palm farming will be seen from the People's Business Credit given to farmers with the aim of increasing farmers' capital in developing oil palm farming and increasing their income by maximizing the use of land and fertilizer in oil palm farming so as to increase the production of oil palm farming in Langkat Regency. This study aims to analyze the effect of oil palm farming production on people's business credit, land area, and fertilizer in Langkat Regency. Respondents were interviewed directly as many as 50 coconut farmers. The data analysis used was multiple linear regression with E-Views 10. The results showed that people's business credit, land area, and fertilizer simultaneously (together) influence the production of oil palm farming. People's business credit has a positive effect on increasing the production of oil palm farming, people's business credit which is used for production activities can directly increase the production of oil palm farming. Oil palm land area has a positive effect on increasing oil palm farming production, the area of ​​oil palm farming land, the higher the yield of palm oil production. Fertilizer has a positive effect on increasing the production of oil palm farming.